4′-Methyl-4,5′-bithiazole-based correctors of defective ΔF508-CFTR cellular processing - Yoo, Choong Leol (2008)
The synthesis and ΔF508-CFTR corrector activity of a 148-member methylbithiazole-based library is reported. Synthetic routes were devised and optimized to generate methylbithiazole analogs in four steps. Corrector potency and efficacy was assayed using epithelial cells expressing human ΔF508-CFTR. These structure-activity data establish that the bithiazole substructure plays a critical function; eight novel methylbithiazole correctors were identified with low micromolar potencies.